PENGARUH MINAT BERWIRAUSAHA TERHADAP PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI KABUPATEN SUMBAWA - Hikmawati, Nurul; Suprianto, S; Ismawati , I (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to know the effect of entrepreneurial interest on the seaweed cultivation development (Study in Tanjung Bele Hamlet, Olat Rawa Village, Moyo Hilir Sub-District). This research uses a causal associative design, namely research that aims to determine the relationship between two or more variables. The data used in this research is quantitative data in the form of scores from respondents' responses in answering the questions given. This data was obtained directly by researchers from primary sources collected through questionnaires. Determining the sample in this study used census sampling techniques, this is because the population is relatively small, namely 36 people, making it possible for researchers to study all the elements in the research area. The data that has been collected will be tabulated and then processed using the SPSS application to be studied using techniques that include simple linear regression analysis techniques, partial hypothesis testing (t test), and determinant coefficient test (R2). The results of the study showed that the Entrepreneurial interest has a positive and significant influence on the development of seaweed cultivation in Tanjung Bele Hamlet. The variable interest in entrepreneurship has quite a large ability to influence changes in the development of seaweed cultivation variables in Tanjung Bele Hamlet, namely 54.2%, while the remaining 45.8% is influenced by other variables outside this research model, such as capital, labor, land area and experience in seaweed cultivation business.